The EU Adventures of 'Herculex': Report on the EU Authorization of the Genetically Modified Maize 1507. (June 2014) - Weimer, Maria; Pisani, Gaia
Abstract : The EU authorization process of the insect-resistant maize 1507, branded by its developer company Pioneer-DuPont as 'Herculex', is perhaps the most interesting and emblematic example of the current regulatory crisis of GMO regulation in Europe. The case is particularly controversial, because it concerns the first risk assessment regarding the cultivation of a GMO issued by the European Food Safety Authority (EFSA) since its establishment in 2005. It involves a long and complicated authorization process marked by persistent contestation of both the EFSA's risk assessment and the Commission's risk management; a total of six EFSA opinions; administrative delay; and ultimately a judicial condemnation of the Commission's behavior by the EU General Court. This case is of particular relevance, because it registers a slight yet meaningful change in the EFSA's approach to GMO risk assessment including the way the EFSA has dealt with competing scientific opinions, risks and uncertainty involved in GMO regulation. Moreover, in the field of GMO authorizations under the new legislative framework, the European Parliament (EP) has actively intervened in the administrative authorization process. It should be noted that the outcome of this process remains unclear at the moment, given that at the time of writing the Commission has not yet taken its final decision on Maize 1507. The present report aims to offer an overview of this year-long and controversial process including the approaches taken by the relevant institutions involved therein.